2008
DOI: 10.1002/adma.200701577
|View full text |Cite
|
Sign up to set email alerts
|

Well Ordered Polymer Melts from Blends of Disordered Triblock Copolymer Surfactants and Functional Homopolymers

Abstract: Microphase segregated block copolymer melts and solids have long garnered significant scientific interest due to their ability to spontaneously form periodic morphologies at controllable length scales. [1][2][3] Their utility as stand-alone nanostructured functional materials [4][5][6][7][8] or as templates for the fabrication of hierarchical solids [9][10][11][12] is well documented.However, their deployment in large scale applications has often been limited by the cost and scalability of the living polymeriz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
102
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 77 publications
(111 citation statements)
references
References 32 publications
9
102
0
Order By: Relevance
“…Tirumula et al 47 recently showed that the addition of a homopolymer with a selective interaction for one of the blocks has the same effect. This effect also applies to diluted blends 45 and this simple rule of thumb thus has wide applicability.…”
Section: Discussionmentioning
confidence: 99%
“…Tirumula et al 47 recently showed that the addition of a homopolymer with a selective interaction for one of the blocks has the same effect. This effect also applies to diluted blends 45 and this simple rule of thumb thus has wide applicability.…”
Section: Discussionmentioning
confidence: 99%
“…This attribute, which distinguished such nanoparticles from small nanoparticles or simple low molar mass molecules that interact only by van der Waals forces, is experimentally observed and theoretically predicted. In this spirit, we note that independent studies have shown that the stability of block copolymer nanostructures can likewise be enhanced through the incorporation of selective 37 or functional 38 homopolymers that remain mixed within (and do not macrophase-separate from) the copolymer nanostructure. Addition of selective nanoparticles to ordered block copolymers may therefore not only yield novel, spatially-modulated hybrid materials via nanoparticle assembly 39 for a wide variety of growing nanotechnologies, but also provide an alternative physical means by which to promote polymeric nanostructure development.…”
mentioning
confidence: 89%
“…In aqueous solution, without silicate ions, the interaction between PPO and PEO of Pluronic copolymers (PEO-PPO-PEO) is only weakly repulsive [46]. It has been reported that the blending of PEO-based copolymers with some additives (inorganic salts or PAA) could induce an increase of incompatibility toward the other block [34,[47][48][49]. The association of PEO segments and oligosilicates increase the effective incompatibility between PPO segments and PEO-silicate segments.…”
Section: Factors Of Segregation Model-vnmentioning
confidence: 99%